ORA ET LABORA SPIRITUALITAS DOA DAN KERJA DALAM HIDUP DAN KARYA PAULUS - Yosef Masan Toron (Jurnal Alternatif Wacana Ilmiah Interkultural, 2013)
Ora et Labora has been wellknown in Church History as a way of living a life very much based on the Bible. No spiritual life without praying and at the same time no spirituality without labour . Christian spirituality has been woven with prayer life dan with a serious commitment to dayly labour whatsoever.These two dimension was verymuch shown bythe life of St.Paul, the great Apostle and missionary.Paul according to the article is a man of prayer and at the same time a man of labour.Prayer is always a felt need for an apostolic work meanwhile labour is always an anwer for the economic poverty of men and at the same time “homo faber" is a rich illustration for our vows of poverty in the Church.